IMPLEMENTASI JSON PARSER PADA LOGIN PAGE UNTUK AUTENTIKASI USER APLIKASI MOBILE - Bersama Sinuraya; Denny Hasmita Maha (UPPM, 2019)
Mobile programming is currently experiencing rapid growth in various circles, especially in Indonesia. Almost all government and private agencies use online systems in addition to websites as well as systems that are based on mobile. Therefore this study focuses on how to create applications for user authentication on the login page on an Android smartphone, by retrieving user data and passwords that have been registered in the database, using the HTTP Connection and JSON Parsing methods. Making applications using the Java programming language, with the help of IDE Eclipse tools and MySQL for database servers. JSON communicating through the Application Program Interface (API) aims to connect mobile applications with databases on the server. In this study the API is a collection of PHP source code, the contents of which are queries to retrieve data from the database, the results of which are encoded in JSON form